2011
DOI: 10.1063/1.3553933
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy in bulk nanocrystalline SmCo5 permanent magnet prepared by hot deformation

Abstract: Bulk anisotropic nanocrystalline SmCo5 magnets have been prepared by hot deformation method. The height reduction of the magnets plays a key role in inducing the crystallographic alignment in the magnet. Increase of height reduction to 90% leads to the formation of platelet shape grains perpendicular to the press direction; correspondingly c-axis crystallographic texture and magnetic anisotropy were developed in the deformed magnets. The coercivity of the magnets increases first,and then decreases again with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…The second method is referred to the analysis of emission spectra at room temperature. It is noteworthy to mention that in the case of Eu 3+ -doped nontransparent hosts, we are not always able to measure the absorption spectra [40,41]. Therefore, for Gd 2 O 3 :Eu 3+ nanoplatelets, the second method allows the calculation of J-O parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second method is referred to the analysis of emission spectra at room temperature. It is noteworthy to mention that in the case of Eu 3+ -doped nontransparent hosts, we are not always able to measure the absorption spectra [40,41]. Therefore, for Gd 2 O 3 :Eu 3+ nanoplatelets, the second method allows the calculation of J-O parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the values of Ω k can be calculated using the emissions of 5 D 0 → 7 F J ' ( J ' = 2, 4, 6). The results of our calculations are shown in Table 3 together with the Ω k values of Eu 3+ ions in other hosts [41,51-57]. …”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] In particular, (BH) max values exceeding the theoretical limit of SmCo 5 have been reported in multi-layered and tri-layered SmCo 5 /a-Fe films, 11,12 which suggests that a layered structure has an advantage in controlling a microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…The other R-Co hard magnetic compound, rhombohedral Sm 2 Co 17 , showed no deformationinduced texture, at least when upset by up to 70% [5]. Recently, Yue et al [6] reported that a significantly improved texture can be obtained in the nanocrystalline SmCo 5 alloys subjected to dieupsetting at a very high degree of deformation (more than 85% height reduction). In this paper, we report the effect of high degree deformation on the texture and magnetic properties of nanocrystalline alloys based on the PrCo 5 , SmCo 5 and Sm 2 Co 17 compounds.…”
Section: Introductionmentioning
confidence: 97%